Computer Program for Point Group Analysis - Arora, Kishor (Asian Journal of Chemistry, 2016)
Symmetry and point group analysis for various molecules is one of the important parts in understanding the spectroscopic and other related properties of the substance. This is also an important portion of the curricula of the undergraduate as well as postgraduate classes. It is necessary for a student of chemistry to have a knowledge of how to locate the symmetry elements in a particular molecule and to arrive at its right point group. The present paper reports a computer program in most interactive BASIC language on Pentium IV compatible PC which can be used as teaching aid material for instructing the students.